Exploring the impact of social inequality and poverty on the mental health and wellbeing and attainment of children and young people in Scotland. (November 2019) - Mowat, Joan Gaynor
The poverty-related attainment gap is an internationally recognised problem. There is growing recognition that it cannot either be understood or addressed without taking cognisance of children's mental health and wellbeing. The focus of this conceptual article is to examine the impact of social inequality and poverty on the mental health and wellbeing and attainment of children and young people in Scotland through the lens of resilience. While not a 'state of the art' literature review, a systematic approach was adopted in the selection of the literature and in the identification of themes to emerge from it. A range of risk and protective factors at the individual, social, societal and political levels emerged as impacting on the mental health and wellbeing and attainment of children living in poverty, and three important mediating variables are the negative impact of social stratification and adverse childhood experiences and the positive impact of a supportive adult. Schools alone cannot solve the problem. The findings revealed that there is a need to build a strong infrastructure around families and schools and to examine how economic, social, health and educational policy interact with each other as a starting point in addressing the problem, supported by inter-disciplinary research.